BYS10, a novel selective RET inhibitor, exhibits potent antitumor activity in preclinical models - Qin, Fei; Chen, Yiman; Deng, Jinhai; Guo, Ruizhi; Xie, Zhoufan; Luo, Zhibo; Wang, Lin; Huang, Tianbai; Zhao, Jiaji; Wang, Jiansong; Bao, Yingxia (Frontiers in Pharmacology, 2025)
BackgroundAberrant alterations in the RET gene serve as oncogenic drivers in multiple cancers, making RET kinase inhibition a promising therapeutic strategy. However, acquired resistance limits the clinical efficacy of selective RET inhibitors.MethodsEnzymatic assays were used to measure the IC50 of BYS10 against wild-type RET and six mutants/fusions. The anti-RET activity of BYS10 was systematically evaluated through in vitro (cell proliferation inhibition assays) and in vivo (RET-altered xenograft models) experiments. RET phosphorylation inhibition by BYS10 was confirmed via Western blot, and optimized binding for RET G810R/S potent inhibition was verified by molecular docking.ResultsIn enzymatic assays, BYS10 showed low nanomolar potency against wild type RET and six clinically relevant RET mutations/fusions, including RET G810R/S (IC50 0.01–3.47 nM) and RET V804M/L (IC50 2.18–2.65 nM). BYS10 also displayed significant anti-proliferative activity across a panel of RET-altered cell lines, including the inhibition of Ba/F3-KIF5B-RET-G810R/S (IC50 25.94–240.60 nM) and Ba/F3-KIF5B-RET-V804M/L (IC50 13.38–46.09 nM). Supported by favorable pharmacokinetics, BYS10 achieved robust anti-tumor efficacy in diverse RET-driven xenograft models. In Ba/F3-KIF5B-RET xenograft model, BYS10 at 3 mg/kg achieved a TGI% of 78.45%, versus 57.06% for Selpercatinib (P < 0.001). In Ba/F3-KIF5B-RET-V804L xenograft model, BYS10 at 3 mg/kg achieved a TGI% of 94.67%, versus 79.48% for Selpercatinib (P < 0.05). In Ba/F3-KIF5B-RET G810R xenograft model, BYS10 at 10 mg/kg achieved a TGI% of 65.96%, versus 35.37% for Selpercatinib (P < 0.001). In Ba/F3-KIF5B-RET G810S xenograft model, BYS10 at 10 mg/kg achieved a TGI% of 112.59%, versus 82.15% for Selpercatinib (P < 0.001). Western blot analysis confirmed potent suppression of RET phosphorylation by BYS10. Molecular docking analysis confirmed that BYS10 achieves potent inhibition of RET G810R/S proteins through an optimized binding mode.ConclusionCollectively, BYS10 represents a novel, highly selective RET inhibitor with superior in vitro and in vivo activity against multiple RET alterations compared to Selpercatinib. Its recent Investigational New Drug (IND) approvals from the FDA and NMPA underscore its therapeutic potential for RET-driven malignancies.